KONDISI SOSIAL EKONOMI MASYARAKAT SEBELUM DAN SESUDAH BERDIRINYA PT. BINA PRATAMA SAKATO JAYA SOLOK SELATAN 1 (BPSJ-SS1) DI KANAGARIAN ABAI KECAMATAN SANGIR BATANG HARI KABUPATEN SOLOK SELATAN - Suriati, Afrina; Rianto, Slamet; Nefilinda, Nefilinda (Pendidikan Geografi, 2013)
South Solok regency is one of regencies in West Sumatra province that has the potential to produce Natural Resources (SDA). In addition to working in the agricultural sector are also people working in the sector, namely oil palm plantations. Producing region is the famous palm oil palm plantations are in Abai District Kanagarian Sangir Batang Hari and the establishment of PT. Bina Pratama Sakato Jaya South Solok 1 (BPSJ SS-1). This study aims to information on Socio-Economic Conditions Before and After Establishment PT.BPSJ SS-1 In Kanagarian Abai district Sangir Batang Hari Regency South Solok. This study discusses the state of education, livelihood condition, condition and condition of welfare income.The population is all the people who work in PT.BPSJ SS-1 amounted to 1025, respondents in the study sample is taken proportional random sampling of 100% of the total population is 102 people .The results include : Â ) Prior to the establishment of PT.BPSJ SS-1 with the condition of public education (36.3%) did not complete primary school, after the founding of PT.BPSJ SS-1 bring positive change to the condition of their childrens education is to graduate high school with (47.1%) , 2) Prior to the founding of PT.BPSJ SS-1 livelihood farming conditions (57.8%) , after the establishment of PT.BPSJ SS - 1 positive bring changes to the conditions of most peoples livelihood as factory workers in PT.BPSJ SS-1, 3) Prior to the establishment of its income PT.BPSJ SS-1 under < USD. Rp. 1,000,000 monthly (80.4%), after the founding of PT.BPSJ SS-1 positive bring Â to conditions incomes between Rp.1000000-2000000 monthly (74.5%), 4) Prior to the founding of PT.BPSJ SS-1 community welfare conditions have not been prosperous in terms of clothing, food, shelter and her health, after the founding of PT.BPSJ SS-1 bring change positively to the level of social welfare and health before the founding of capability PT.BPSJ SS-1 present a cost for treatment is still poor (72.7 %) and more people take to the healer if there is a family illness, after the establishment of PT.BPSJ SS-1 been able to provide costs for treatment (80.4%) and the public has been able to bring to the family doctor when someone is sick.